Cervical cancer prevention using HPV vaccination and acetic acid visual inspection screening - Didik Setiawan; Githa Fungie Galistiani; Tasya Firda Adabiyah (Universitas Muhammadiyah Magelang, 2025)
Cervical cancer is a significant global health problem and one of the leading causes of death among women in various countries. To address the increasing cases of this disease, this community service initiative collaborates with PKU Muhammadiyah Gombong Hospital to conduct counseling sessions. The purpose of this activity is to enhance public knowledge about cervical cancer prevention and encourage participation in Visual Inspection of Acetic Acid (IVA) screening within the hospital's service area. Prevention measures are implemented through HPV vaccination and IVA screening, along with the distribution of health promotion materials in the form of leaflets and booklets. The results of the activity showed that participants achieved an average score of 11.38 out of 20, and nearly 50% of them expressed a willingness to undergo the IVA test, indicating an increase in knowledge. In conclusion, this service activity led to an increase in the Kebumen Regency community's knowledge and interest regarding screening and vaccination for cervical cancer prevention.